Funcionalização do grafeno por ácidos fosfônicos: estudos por primeiros princípios - Regiane do Nascimento (2011)
The functionalization (physical or chemical modification) of graphene, which is a zero-gap semiconductor, may significantly change its electronic properties, resulting, for instance, in metallic or non-null gap semiconductor behaviors. Among the several possible ways to functionalize graphene, we investigate here one of large current interest; the Self-AssembledMonolayers-SAMs. We consider SAMs of phosphonic acids with a general chemical formula CH3(CH2)n PO(OH)2; specifically, we will consider the OctadecylPhosphonic Acid (OPA, n =17), the TetradecylPhosphonic Acid (TPA, n =13), and the Octyl Phosphonic Acid (OcPA, n =7). In recent experimental works [13], it was observed that the phosphonic acids OPA, TPA and OcPA form similar structures when deposited on substrates - Self-Assembled Bilayers (SABs, or bilayers). We investigated, by means of first principles calculations based on Density Functional Theory (DFT), the energetics and the structural properties of graphene with adsorbed bilayers of TPA, OPA and OcPA acids. We studied several possible configurations for dimers deposited along two distinct directions of graphene: armchair e zigzag. Our calculations show that the preferred orientations of all dimers of the studied molecules atop graphene are along the zigzag direction, and that the bilayers should remove electrons from graphene (hole doping). Both predictions are consistent with experimental results.